A thin line between love and hate. Leonardville and Riley: the evolution of a small town rivalry - Schnee, Angela (Kansas State University. Dept. of History, 2011)
The author recreates the formation of a twin town rivalry in Riley County, Kansas. She explores how the rivalry between Riley and Leonardville, Kansas first began over a century ago and the reasons why it still exists today. The author uses a variety of sources such as historical texts, newspaper articles, and personal interviews to create a portrait of the rivalry between the two towns.
Keywords: Riley County; Riley; Leonardville; Twin towns; Town rivalry; Railroad towns